2018
DOI: 10.1016/j.schres.2018.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Suspiciousness in young minds: Convergent evidence from non-clinical, clinical and community twin samples

Abstract: Social mistrust assessed by the SMS may be heritable. The SMS demonstrates good discriminant validity with clinical diagnoses of schizophrenia. However, it seems to be correlated with multiple aspects of psychopathology in the schizophrenia group, rather than being specific to delusional ideation/paranoia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The results highlight the role of environmental factors in influencing how adolescent PENS develop, which adds to existing research that has shown the importance of environmental factors at single time points (Hur, Cherny, & Sham, ; Zavos et al., ; Zhou et al., ). Of particular interest in this context are our results that nonshared environment contributes to more than a third of the stability of PENS (except PRNS).…”
Section: Discussionsupporting
confidence: 61%
“…The results highlight the role of environmental factors in influencing how adolescent PENS develop, which adds to existing research that has shown the importance of environmental factors at single time points (Hur, Cherny, & Sham, ; Zavos et al., ; Zhou et al., ). Of particular interest in this context are our results that nonshared environment contributes to more than a third of the stability of PENS (except PRNS).…”
Section: Discussionsupporting
confidence: 61%
“…A systematic review of 19 general population studies showed that younger children (9-12 years) generally report higher prevalence rates of psychotic-like experiences (PLEs) than older children (13-18 years), at 17% and 7.5%, respectively (Kelleher et al, 2012). More recent cross-sectional studies of school children have either replicated this age contrast -reporting higher prevalence rates in childhood at 8 to 10 years and a leveling off in adolescence, at 11 to 14 years (Wong et al, 2014) -or reported no age contrast in the same age range (Zhou et al, 2018). Why more PLEs may be reported in childhood than in adolescence may be explained by three reasons: First, it may be due to the still developing subcortical regions of children's brains.…”
Section: Introductionmentioning
confidence: 99%
“…From adolescence, all bases and domains are extended to less proximal targets and more general themes such as politics and others (Rotenberg, 2019). Zhou et al (2018) and Sakai (2010) investigated the role of genetic and environmental factors in twin studies and found that shared and nonshared environments contribute to trust belief development. Rotenberg (2019) points out that attachment seems to be a relevant environmental factor that influences the formation of IT.…”
Section: From Epistemic To Interpersonal Trustmentioning
confidence: 99%